Một số phương pháp và thuật toán nhận dạng chữ - Kiem, Hoang; Thang, Giang Vu; Dien, Nguyen Van (Journal of Computer Science and Cybernetics, 2018)
In this paper, some methods preprocessing the characters were presented in order to improve the quality of recognition processes. At the same time, three our effective character recognition algorithms were described in detail, too. First experiments were perpormed with a help of PC computer and Microtek scanner on four widely-used fonts of characters. The first results with a high quality of character recognition have been received, that confirms the correctness and effectness of four applied algorithms.